Coffee culture in Indonesia : a symbolic interactionism point of view - Melly Ridaryanthi,; Abdul Latiff Ahmad,; Dwityas, Nindyta Aisyah (Penerbit Universiti Kebangsaan Malaysia, 2022)
The coffee industry has evolved in several waves which resulted in coffee culture among a culturally diverse society. Drinking coffee culture has taken part in consumers’ daily life not only as cultural drinking, and routine but also as a medium for interaction and communication. Millennials are seen as a group of society who consume coffee on a day to day basis. The issues highlighted in this study is regarding how the meaning of drinking coffee is constructed and shared among millennial as coffee consumers through their interaction and communication. This is a phenomenological study conducted based on the constructivism paradigm whereby a qualitative approach is employed. Five (5) focus group discussions with a total of 23 informants were conducted. A snowball sampling process was applied to identify participants in this study based on the characteristics defined, whilst Symbolic Interactionism Theory is used to guide the study. Discussion is presented towards textural and structural descriptions of coffee culture meaning. Findings show that coffee culture is seen both as personal and social construction of meanings. Interactions with surroundings have given experience whereby individuals created the construction of drinking coffee as a personal journey and social tool for interaction.